Recommended fertilization and timing of nitrogen fertilization influences the morphogenesis, structural characteristics, and production efficiency of Mombaça grass - Harry Sousa Paiva; Sheila Vilarindo de Sousa; Ellen Cristina de Araújo da Conceição; Antônio Clementino dos Santos; Ricardo Shigueru Okumura; Rafael Mezzomo; Perlon Maia dos Santos; Raylon Pereira Maciel (Acta Scientiarum. Animal Sciences, 2023)
This study aimed to evaluate whether different fertilization strategies influence the morphogenic, structural, and production characteristics of Megathyrsus maximus cv. Mombaça. The experimental design adopted was a randomized block design with a 4 × 3 factorial scheme having five replications. The treatments were as per the following fertilization recommendations: 5th Approach Guide (5AP), Pará Guide (PG), Nutrient Replacement (RP), and the Michaelis and Menten adapted model (MM), applied for three days after application of the nitrogen (N) source following defoliation (days 0, 3, and 6). The interaction between factors affected the following variables: leaf appearance rate (LAR), leaf elongation rate (LER), and leaf senescence rate (LSR). The highest stem elongation rate (SER) was observed for the 5AP recommendation treatment with N application on day 0 (0.113 cm). The highest leaf area index (LAI; 5.33) and tiller population density (TPD; 421.5 tillers m-2) were observed for the 5AP recommendation. The 5AP recommendation with N application on day 0 and on the sixth day after defoliation, and the MM recommendation with fertilization on day 0 showed the best LAR and LER, as well as a greater number of cycles and greater absolute values of leaf blade dry mass.